Flow visualization of the transient effect of the internal two-phase flow on the external iso-pentane flashing spray under different injection pressure. (1st February 2023) - Wang, Jiafeng; Zhou, Zhifu; Chen, Bin; Yang, Tao; Zhang, Lu; Romeos, Alexandros; Giannadakis, Athanasios; Panidis, Thrassos
Graphical abstract: Highlights: Internal flow and iso-pentane spray of different injection pressure were visualized. A shattering index is put forward to dominate the spray pattern conversion. A correlation between the spray cone angle and the shattering index is proposed. High-void-fraction internal flow raises spray cone angle and droplet concentration. Lower shattering index yields slower change but larger increase of radial expansion. Abstract: Flashing spray occurs when the saturated liquid is discharged into a gaseous environment at an ambient pressure lower than its saturation pressure. Internal flow is a primary determinant on the behavior of external flashing spray, so its transient effect was investigated with iso-pentane as working medium. The coupled effect of superheat level and injection pressure was comprehensively explored with initial temperature from 30 °C to 70 °C and injection pressure from 1.2 MPa to 2.4 MPa. Under different injection pressure, the stable spray patterns can still be categorized as non-shattering, partially shattering, completely shattering and flare flashing separated by the shattering index X ·( Pinj / Pa ) 0.5 of 0.21, 0.39 and 0.76, which represents the product of homogeneous nucleation rate and the ratio of injection pressure over ambient pressure. A strong correlation between the spray cone angle and the shattering index is proposed as a piecewise function separated by X ·( Pinj / Pa ) 0.5  = 0.39. High-void-fraction internal two-phase flow is easier to be formed in partially shattering or completely shattering pattern, which would lead to a hysteretic flashing spray with a significant increase of spray cone angle and droplets concentration. Low X ·( Pinj / Pa ) 0.5 yields slower response of external morphological changes but larger enhancement of radial expansion.